INTERMEDIALITY IN FANDOM CULTURE: THE IMPACT OF BTS ON KOREAN LITERATURE READING HABITS: FOCUSING ON INDONESIAN ARMY - Setyaningsih, Nining; Latifah, Eva (WILAYAH: The International Journal of East Asian Studies, 2024)
Fandom forms cultural spaces where audiences unite. This article introduces fan activities influenced by idols, discussed and shared in affinity spaces. It offers a theoretical framework, focusing on BTS fandom (ARMY) reading habits in Korean literature. This model highlights content intermediality's importance in analyzing media content within fandom culture. Using content analysis and digital ethnography methods, this study examines Indonesian ARMY fandom through the @IARC_twt twitter account. Results reveal productive reading activities within the Indonesian BTS ARMY fandom, including build reading habit through sub community in twitter, transmedia storytelling through idol reading lists, and hashtag-sharing. These activities also promote books related to BTS album themes and Korean literature to the public. Furthermore, the article explores the positive impact within fandom culture and conceptualizes a productive fandom model.